PERAN GURU BK/KONSELOR DALAM MEMBANTU SISWA MENGHADAPI MASA PUBERTAS - Ramdhani, Ramdhani (Jurnal Konselor, 2015)
Adolescence is a period in which the development and rapid growth. This change is also commonly called as puberty. The changes experienced by teenagers on puberty often make them restless. As a matter of fact, counseling teachers / counselors have an enormous role in helping students overcome the puberty. This role is reflected from counseling service given to help students face puberty so it can create good judgment of puberty. Hence, the teenagers will have a positive self-concept in his life.